Impact of kidney volume on incidence of in-hospital kidney-related adverse outcomes in patients with acute heart failure - Akira Saito; Taku Asano; Nobuyuki Komiyama; Sachiko Ohde (BMC Cardiovascular Disorders)
Abstract Background Recent studies revealed an association between small kidney volume and progression of kidney dysfunction in particular settings such as kidney transplantation and transcatheter aortic valve implantation. We hypothesized that kidney volume was associated with the incidence of kidney-related adverse outcomes such as worsening renal function (WRF) in patients with acute heart failure (AHF). Methods This study was a single-center retrospective cohort study. It included patients admitted for AHF treatment between 2011 and 2021 and who underwent computed tomography (CT) that included images of the kidneys on the date of admission. We measured the volume of the right and left kidneys using dedicated volume analyzing software for 3D-CT (SYNAPSE VINCENT, Fuji Film, Tokyo, Japan) and determined the total kidney volume by adding the volumes of the left and right kidneys. We defined the composite of death from any cause, initiating renal replacement therapy, and WRF during hospitalization as major adverse kidney events (MAKE). We conducted multivariate logistic regression analysis to evaluate the impact of MAKE and each component of MAKE adjusted for age, sex, body surface area, estimated Glomerular Filtration Rate (eGFR) on admission date and the factors that were significantly associated with the incidence of MAKE by bivariate analysis. Results In the 229 patients enrolled in the analysis, death from any cause, initiating RRT, and WRF occurred in 30 (13.1%), 10 (4.4%), and 85 (37.3%) patients, respectively. It was found that small kidney volume (≤ 250 ml) was independently associated with the increased incidence of MAKE (odds ratio 3.92, 95% confidence interval [1.18–13.08], p = 0.026) and WRF (odds ratio 6.58, 95%confidence interval [1.85–23.42] p = 0.004). The area under the receiver operating characteristic curve for multivariate logistic regression analysis of MAKE was 0.71. Conclusions Kidney volume on admission was independently associated with the increased incidence of kidney-related adverse outcomes during hospitalization in patients with AHF.